1988
DOI: 10.1007/bf00283727
|View full text |Cite
|
Sign up to set email alerts
|

Molecular nature of genetic changes resulting in loss of heterozygosity of chromosome 11 in Wilms' tumours

Abstract: In this paper we describe the analysis of genetic changes in chromosome 11 in Wilms' tumours. Using a range of probes for regions 11p15, 11p13 and 11q we have screened DNA from 14 Wilms' tumours together with control DNA obtained from the patients' lymphocytes and their parents. We have been able to demonstrate loss of heterozygosity in 5 of the 14 different Wilms' tumours. In three of these five tumours, loss of heterozygosity did not involve markers for 11p13, 11p15.4 or the proximal region of 11p15.5, but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
1
3

Year Published

1993
1993
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(72 citation statements)
references
References 70 publications
0
68
1
3
Order By: Relevance
“…p57 kip2 is a cyclin dependent kinase-cyclin complex inhibitor that causes G 1 arrest and is subjected to paternal imprinting. Paternal isodisomy of chromosome 11 is a phenomenon frequently found in studies of both RMS (Scrable et al, 1989a) and Wilms' tumor (Mannens et al, 1988) and should result in a low expression of p57 kip2 and subsequent a decrease of inhibition of cdkcyclin complexes and progression through the cell cycle. In di erent tumors including RMS no gross rearrangements of p57 kip2 or mutations in the coding region have been found (Orlow et al, 1996;Tokino et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…p57 kip2 is a cyclin dependent kinase-cyclin complex inhibitor that causes G 1 arrest and is subjected to paternal imprinting. Paternal isodisomy of chromosome 11 is a phenomenon frequently found in studies of both RMS (Scrable et al, 1989a) and Wilms' tumor (Mannens et al, 1988) and should result in a low expression of p57 kip2 and subsequent a decrease of inhibition of cdkcyclin complexes and progression through the cell cycle. In di erent tumors including RMS no gross rearrangements of p57 kip2 or mutations in the coding region have been found (Orlow et al, 1996;Tokino et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Following on from these observations, loss of heterozygosity (LOH) studies, which are now generally accepted as indicating the sites of tumour suppressor genes (Cavenee et al, 1983;Coppes et al, 1994), demonstrated that only 25% of sporadic WT showed loss of alleles for markers on 11p and, in some cases this LOH was restricted to the more distal 11p15 region. Thus, it is now clear that there are at least two separate loci on the short arm of chromosome 11 (in 11p13 and 11p15) which are likely to be involved in Wilms tumorigenesis (Mannens et al, 1988;1990;Coppes et al, 1992a;Reeve et al, 1989;Wadey et al, 1990). More recently, LOH along the long arm of chromosome 16 has been identi®ed in approximately 20% of tumours (Austruy et al, 1995;Coppes et al, 1992;Grundy et al, 1994;Maw et al, 1986), implicating yet another chromosome locus for WT, although in this case it appears to be involved more in progression rather than initiation, since the LOH was associated with more aggressive tumours .…”
Section: Introductionmentioning
confidence: 99%
“…The observation of preferential loss of maternal alleles from the short arm of chromosome 11 (1 lp) in tumours that show loss of heterozygosity (Mannens et al, 1988;Pal et al, 1990;Coppes et al, 1992) implies that primary mutation on lip preferentially occurs on the paternally derived chromosome and suggests that the paternally derived allele is more mutable than the maternal one (Huff et al, 1990;Coppes et al, 1992). To investigate whether germinal mutations are seen with equal frequency in maternally vs paternally inherited chromosomes, Huff et al (1990) examined the parental origin of eight cases of de novo constitutional deletions of 1lpl3 and found that seven were of paternal origin.…”
mentioning
confidence: 99%